ASIMETRI INFORMASI, UKURAN PERUSAHAAN DAN PENGARUHNYA TERHADAP PRAKTIK MANANJEMEN LABA - Verliani Dasmaran; Andi Odeh (Universitas Kristen Krida Wacana, 2020)
The research objective is to find out how the information between management and shareholders can affect earnings management in the company. As well as how the size of the company indicated by the size of the company from total assets can affect earnings management practices in mining companies that have been listed on the market in 2019. The research method used in this research is a quantitative research method with an associative approach. The results of the research show that information asymmetry has a positive but not significant effect on management earnings. The size of the firm is proven to have a negative effect on earnings management practices. The research contribution is expected to provide information related to the information obtained and the size of the company that can affect earnings management in the company. Keywords: MIS information, size, earnings management